Characterization of optical clearing mechanisms in muscle during treatment with glycerol and gadobutrol solutions. Issue 1 (23rd September 2022) - Silva, Hugo F.; Martins, Inês S.; Bogdanov, Alexei A.; Tuchin, Valery V.; Oliveira, Luís M.
Abstract: The recent increasing interest in the application of radiology contrasting agents to create transparency in biological tissues implies that the diffusion properties of those agents need evaluation. The comparison of those properties with the ones obtained for other optical clearing agents allows to perform an optimized agent selection to create optimized transparency in clinical applications. In this study, the evaluation and comparison of the diffusion properties of gadobutrol and glycerol in skeletal muscle was made, showing that although gadobutrol has a higher molar mass than glycerol, its low viscosity allows for a faster diffusion in the muscle. The characterization of the tissue dehydration and refractive index matching mechanisms of optical clearing was made in skeletal muscle, namely by the estimation of the diffusion coefficients for water, glycerol and gadobutrol. The estimated tortuosity values of glycerol (2.2) and of gadobutrol (1.7) showed a longer path‐length for glycerol in the muscle. Abstract : The evaluation of the optical clearing (OC) mechanisms created in tissues both by common transparency and radiology contrasting agents is necessary for comparison and to characterize the molecular diffusion of such agents. Measuring sequential spectra of muscle samples under treatment with glycerol and gadobutrol solutions, it was possible to characterize the OC mechanisms and evaluate the tortuosity parameter for these agents, which is smaller for gadobutrol.